2013
DOI: 10.1371/journal.pone.0068482
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Intussusception: A Literature Review

Abstract: BackgroundPostlicensure data has identified a causal link between rotavirus vaccines and intussusception in some settings. As rotavirus vaccines are introduced globally, monitoring intussusception will be crucial for ensuring safety of the vaccine programs.MethodsTo obtain updated information on background rates and clinical management of intussusception, we reviewed studies of intussusception in children <18 years of age published since 2002. We assessed the incidence of intussusception by month of life among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
265
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(311 citation statements)
references
References 74 publications
22
265
1
4
Order By: Relevance
“…This is especially worrying in Africa where mortality from intussusception was found to be much higher than in other parts of the world (9% vs <1%). 38 Our findings provide reassurance from a safety perspective for the implementation of rotavirus vaccination, particularly RV1 in Asia, which as a region has lagged behind in introducing the vaccine despite high rotavirus childhood mortality. Unlike other causes of childhood gastroenteritis, improvements in sanitation conditions and water quality are unlikely to reduce the burden of rotavirus in children.…”
Section: Discussionmentioning
confidence: 51%
“…This is especially worrying in Africa where mortality from intussusception was found to be much higher than in other parts of the world (9% vs <1%). 38 Our findings provide reassurance from a safety perspective for the implementation of rotavirus vaccination, particularly RV1 in Asia, which as a region has lagged behind in introducing the vaccine despite high rotavirus childhood mortality. Unlike other causes of childhood gastroenteritis, improvements in sanitation conditions and water quality are unlikely to reduce the burden of rotavirus in children.…”
Section: Discussionmentioning
confidence: 51%
“…Intussusception risk varies across population and regions, 12 and some studies have shown high background rates of intussusception in Spain; 13, 14 a potential association with rotavirus vaccination could cause concern. Thus, our aim was to investigate such association in the Valencia Region, Spain.…”
Section: Manuscriptmentioning
confidence: 99%
“…Juvenile polyps become symptomatic in early childhood, with a peak incidence between 5 and 9 years and, usually, not before the age of two (1). Occurrence is sporadic or within defined syndromes, like Peutz-Jeghers syndrome (mainly small bowel) or juvenile polyposis syndrome (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Intussusception is a common entity in early childhood, with a peak incidence between 5 and 7 months of age (1). However, most cases are ileocolic and idiopathic.…”
Section: Introductionmentioning
confidence: 99%